Cerdik: Screening for Non-Communicable Disease at The Amaory Landfill, Passo Benteng Karang Village - Pollan Versilia Wuritimur; Minnalia Soakakone (Karya Kesehatan Siwalima, 2025)
Non-communicable diseases (NCDs) pose a significant global health challenge. Diabetes mellitus (DM) and hyperuricemia are among the most prevalent non-communicable diseases in Indonesia. Screening is a process to identify both pre- and post-diseases. The purpose of this community service is to detect non-communicable diseases early through blood glucose and hyperuricemia tests. The results of this screening activity indicate that some individuals still have abnormal blood glucose and uric acid levels. This screening is expected to facilitate the early detection of diabetes mellitus (DM) and hyperuricemia, enabling timely treatment and contributing to a healthier and more productive society.